Chemical Profile of Red Dragon Fruit Peel (Hylocereus polyrhizus) by Gas Chromatography - Mass Spectrometry - Anwar, Adillani Nur Mugfirah; Pratama, Mamat; Rahmawati, Rahmawati (Pharmaceutical Reports, 2025)
Red dragon fruit (Hylocereus polyrhizus), a tropical species native to Asia, has gained attention for its potential as a source of bioactive compounds. This study aimed to characterize the chemical constituents present in the peel of H. polyrhizus using gas chromatography–mass spectrometry (GC–MS). The extraction process was performed through maceration with 96% ethanol for four days, followed by filtration and concentration using a rotary vacuum evaporator. The resulting ethanolic extract was analyzed using GC–MS under the following parameters: injector temperature of 250 °C and a programmed column temperature ranging from 70 °C (held for 2 min) to 200 °C at a heating rate of 100 °C/min. The chromatographic analysis identified a total of 82 distinct compounds, indicating the chemical diversity of the extract. Among these, the most abundant peak was detected at a retention time (RT) of 22.806 min, corresponding to pentadecanoic acid (C₁₅H₃₀O₂). The presence of fatty acids, esters, and phenolic derivatives suggests that H. polyrhizus peel may serve as a valuable natural source of antioxidants and other pharmacologically active constituents. Overall, the findings provide fundamental insights into the phytochemical composition of red dragon fruit peel, supporting its potential application in pharmaceutical and nutraceutical formulations.